MAMMOGRAPHY: MASTITIS AND INFLAMMATORY BREAST CANCER (Лучшие интеллектуальные исследования, 2025)
Annotation: Breast cancer is more common in women over the age of 45. Infiltrative breast cancer accounts for 1-5% of all breast cancers. This article reviews the diagnosis of infiltrative breast cancer, mammography and sonoscopy, and the differential diagnosis with mastitis.Аннотация: Рак молочной железы чаще встречается у женщин старше 45 лет. Инфильтративный рак молочной железы встречается в 1–4% случаев среди всех опухолей данной локализации. В статье рассматриваются методы диагностики этого заболевания с использованием маммографии и сонографии, а также проводится дифференциальный анализ инфильтративного рака и мастита.Annotatsiya: Ko‘krak bezi saratoni ko‘pincha 45 yoshdan oshgan ayollarda uchraydi. Infiltrativ ko‘krak bezi saratoni barcha ko‘krak saratoni holatlarining 1–5% ni tashkil qiladi. Ushbu maqolada infiltrativ ko‘krak bezi saratonining diagnostikasi, mammografiya va sonografiya usullari, shuningdek, mastit bilan qiyosiy diagnostikasi ko‘rib chiqiladi.Abstract:  Currently, breast cancer is among the most prevalent malignancies worldwide. In 2022, 2,296,840 individuals were affected by this disease. Inflammatory breast cancer is a rare yet highly aggressive form, accounting for 2–5% of all cases. Our objective is to investigate the clinical, pathological, and mammographic characteristics of this condition and to differentiate it from mastitis at Tashkent Regional Oncology Dispensary. At the Tashkent Regional Oncology Dispensary, we examined 1,000 non-breastfeeding women from March 4, 2024 to November 11, 2024 and 12 of them had IBC. The median age of IBC was 40 years (range 31-65).